2014
DOI: 10.1378/chest.13-2255
|View full text |Cite
|
Sign up to set email alerts
|

Automated Surveillance for Ventilator-Associated Events

Abstract: BACKGROUND: Th e US Centers for Disease Control and Prevention has implemented a new, multitiered defi nition for ventilator-associated events (VAEs) to replace their former defi nition of ventilator-associated pneumonia (VAP). We hypothesized that the new defi nition could be implemented in an automated, effi cient, and reliable manner using the electronic health record and that the new defi nition would identify diff erent patients than those identifi ed under the previous defi nition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 19 publications
5
41
1
2
Order By: Relevance
“…[10][11][12][13][14][15][16]19 The incidence of VAC and IVAC was reported to be approximately 5-10% and 3-5%, respectively, similar to our results (VAC 13.4%, IVAC 5.7%). 10,12,13,19 These previous studies consistently found that the relationship among VAC, IVAC, and con- ventional VAP was poor, and that VAE was associated with adverse outcomes. However, the duration of mechanical ventilation in these studies was shorter than the minimal requirement of 4 d in the VAE definition.…”
Section: Relationship To Previous Studiessupporting
confidence: 91%
“…[10][11][12][13][14][15][16]19 The incidence of VAC and IVAC was reported to be approximately 5-10% and 3-5%, respectively, similar to our results (VAC 13.4%, IVAC 5.7%). 10,12,13,19 These previous studies consistently found that the relationship among VAC, IVAC, and con- ventional VAP was poor, and that VAE was associated with adverse outcomes. However, the duration of mechanical ventilation in these studies was shorter than the minimal requirement of 4 d in the VAE definition.…”
Section: Relationship To Previous Studiessupporting
confidence: 91%
“…Automated surveillance has an accurate, clearly defined medical knowledge base, unlike conventional manual surveillance methods that are based on positive cultures alone and are prone to generate both under-diagnosis (false-negatives) and over-diagnosis (false-positives) [20][21][22]. Conventional manual surveillances have limitations and weakness related to time constraints and human factors such as stress and fatigue, which can all negatively influence decision making.…”
Section: Discussionmentioning
confidence: 99%
“…They affect 5-10% of patients and have consistently been associated with longer duration of mechanical ventilation, longer hospital lengths of stay, more antibiotic usage, and higher mortality rates. [22][23][24][25][26][27][28][29][30][31][32] Multiple studies suggest that patients who develop VAEs are approximately twice as likely to die compared with similar patients who do not develop VAEs. [22][23][24][25][26][27][28][29][30][31][32] …”
Section: Clinical Importancementioning
confidence: 99%
“…Multiple hospitals have now published their experience successfully automating VAE case detection. [27][28][29]31,33 Workers from the Netherlands have pointed out that one can define daily minimum PEEP and F IO 2 in different ways and that this in turn can have a large effect on case detection. 28 Options include the lowest values derived from minute-to-minute ventilator settings, the lowest values derived from paper charts with hourly documentation, or the 10th percentile.…”
Section: Surveillance Efficiencymentioning
confidence: 99%